The selection of migrants and returnees in Romania: Evidence and long-run implications - William Ambrosini; Karin Mayr; Giovanni Peri; Dragos Radu (University of California, Department of Economics, 2012)
This paper uses census and survey data to identify the wage earning ability and the selection of recent Romanian migrants and returnees. We construct measures of selection across skill groups and estimate the average and the skill-specific premium for migration and return for three typical destinations of Romanian migrants after 1990. Once we account for migration costs, we find evidence that the selection and sorting of migrants by skills is driven by different returns in countries of destination. We also find that the return premium increases with migrants' skills and this drives the positive selection of returnees relative to non-migrants. As these findings are consistent with a model of rational choice in the migration decisions, we simulate a rational-agent model of education, migration and return. Our results suggest that for a source country like Romania relatively high rates of temporary migration might have positive long-run effects on average skills and wages.
Keywords: F22; J61; O15; 330; Selection of Migrants; Migration Premium; Returnees